Centers of gravity: The effect of stable shared leadership in top management teams on firm growth and industry evolution - Agarwal, Rajshree; Braguinsky, Serguey; Ohyama, Atsushi (Strategic Management Journal, 2020)
Abstract Research Summary We study the processes of firm growth in the evolution of the Japanese cotton spinning industry during 1883–1914 by integrating strategy and historical approaches and utilizing rich quantitative firm‐level data and detailed business histories. The resultant conceptual model highlights growth outcomes of path dependencies as firms evolve across periods of single versus shared leadership, establish stability in shared leadership, or experience repeated discord‐induced top management team (TMT) leader departures. While most firms do not experience smooth transitions to stable shared TMT leadership, a focus on value creation, in conjunction with talent recruitment and promotion, enabled some firms to achieve stable shared leadership despite discord‐induced departures, engage in long‐term expansion, and emerge as “centers of gravity” for output and talent in the industry. Managerial Summary We demonstrate stable shared leadership is at root of firms who emerge as centers of gravity in an industry and account for the lion's share of output. Stable shared leadership enables growth strategies such as talent recruitment, product diversification, downstream integration, and acquisitions. Stable shared leadership, however, is extremely difficult to maintain. Most firms experience discord‐induced departures in TMTs due to politics and power struggles. Firms that deviate from this norm to become industry leaders achieve stable shared leadership by adhering to fundamental principles related to long‐term value creation as opposed to short‐term gain, adoption of merit‐based promotion systems in defiance of stereotypes, sharing of power within TMT leadership to enable efficient division of labor, and honorable resolution of conflicts and ethical breaches.